Cambios en reconocimiento y medición de las provisiones y revelación pasivos contingentes para las pymes en Colombia. (2020)
The purpose of this work is to carry out an analysis of the International Financial Reporting Standards for SMEs Section 21 provisions and contingencies; make it easier for students and professionals to understand this section and in turn become a practical guide and can apply in their activities. An analysis of contingent provisions and liabilities was initially carried out in the recognition, initial measurement, subsequent measurement and information necessary for disclosure in the Financial Statements. Secondly, the comparison of IFRS for SMEs section 21 and Decree 2649 and 2650 of 1993 is carried out to identify the impact of implementation on contingent provisions and liabilities. Completing this degree work was established by a real case and hypothetical cases of the topic of contingent liabilities for the Tax Tunja Cootax Transport Cooperative; publicizing the accounting treatment according to IFRS for SMEs section 21.